Expansion Strategy Implementation for SMEs - KARAOULANIS, ANDREAS (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The aim of this paper is to introduce some specific strategies SMEs should implement in order to expand to new markets and grow. The author underlines the importance of the three pillars upon which SMEs should establish a concrete strategy. These pillars are the following: adopt disruptive new technologies, focus more on customers and expand into new markets.